Statistical Analysis of the Effect of Aging in Distribution Transformer Insulating Oil on Dielectric Characteristics (LPPM Universitas PGRI Adi Buana Surabaya, 2025)
Transformer oil plays a crucial role as both an electrical insulator and coolant in power distribution systems. Over time, however, it undergoes degradation due to thermal stress, oxidation, and contamination, resulting in a decline in its dielectric properties. This study aims to analyze the impact of aging on the insulating capability of transformer oil and evaluate the effectiveness of purification in restoring its quality. Experiments were conducted on three brands of transformer oil Shell Diala S4, PSP, and Pri Apar in new, aged (in-service), and purified conditions. Breakdown voltage testing was employed alongside Weibull distribution analysis to assess dielectric failure probabilities. The results demonstrate that aged oil exhibits a significant reduction in breakdown voltage, indicating a higher risk of insulation failure. Purification was found to be effective in improving the breakdown voltage of aged oils, restoring their dielectric strength close to or even exceeding that of new oil. Specifically, purified aged Shell Diala S4 oil showed a 70% increase in breakdown voltage, PSP oil improved by 50%, and Pri Apar oil by 47%. Among the tested brands, Shell Diala S4 exhibited the best and most stable dielectric performance both before and after purification. The Weibull analysis confirmed that aged oils have a higher probability of dielectric failure over time, underscoring the importance of regular maintenance. This study recommends periodic purification to maintain the insulating performance of transformer oils and highlights the importance of selecting high-quality oils to ensure long-term system reliability. Shell Diala S4 is recommended for critical and long-term distribution system applications due to its superior insulating performance and greater resistance to degradation. In contrast, PSP and Pri Apar oils, while viable for less demanding applications, should be subject to more frequent monitoring and purification to mitigate the risk of insulation failure.